Levels of emotional awareness during psychotherapy among gynecologic cancer patients. Issue 1 (8th June 2018) - Virtue, Shannon Myers; Manne, Sharon L.; Criswell, Kevin; Kissane, David; Heckman, Carolyn J.; Rotter, David
Abstract: Objective: Emotional awareness is the ability to recognize, describe, and attend to emotions. A known correlate is emotional processing, the ability to orient to and use inner experiences for information. The goal was to examine emotional awareness during therapy among gynecologic cancer patients, identify baseline predictors, and explore the relationship between in-session emotional awareness and processing. Method: Psychotherapy and baseline data from a randomized controlled trial comparing a supportive counseling (SC) intervention and a cognitive-behavioral coping and communication (CCI) intervention were used. The sample was patients with gynecologic cancers randomized to either therapy ( N = 246). Emotion episode transcripts from the first, middle, and sixth of seven in-person sessions were coded for emotional awareness using the Program for Open-Ended Scoring and emotional processing using the Experiencing Scale. Descriptive and regression analyses were conducted. Result: Participants had moderate in-session emotional awareness. SC participants exhibited higher levels of awareness in the first ( p < 0.001) and sixth ( p = 0.002) sessions than CCI participants. Awareness was positively correlated with emotional processing in the first and sixth SC sessions ( r = 0.25 and 0.24, respectively) and all CCI sessions ( r = 0.29–0.31). Baseline negative emotion expression was associated with awareness during the sixth SC session. Baseline cancer-specific distress was associated with awareness during the sixth CCI session. Significance of results: SC may facilitate emotional awareness. Greater emotional awareness in therapy may facilitate emotional processing, which is an important component of most psychotherapies. Patients who are psychologically distressed may exhibit more awareness than others. Similarly, greater emotional awareness may signal greater patient distress.